Epstein-Barr Virus (EBV) infection related thrombocytosis : A Case Report - Adhikari, Suman; Malla, Rewati Raman; Shah, Manoj; Upreti, Ananta; Thapa, Bhawesh (Journal of Advances in Internal Medicine, 2018)
EBV infection can occur worldwide. We managed a 17 year old male who developed transient pancytopenia followed by thrombocytosis concurrent with EBV infection. To the best of our knowledge we have not encountered any cases of thrombocytosis concurrent with EBV infection before. Our case was diagnosed as a case of EBV infection with the help of serology and managed conservatively. In our case, though it is uncommon to find thrombocytosis due to EBV infection, it is possible that following pancytopenia concurrent with the EBV infection, the patient might have developed secondary or reactive thrombocytosis due to elevated endogenous levels of thrombopoietin, interleukin-6, catecholamines.